Intranasal Lipid Nanoparticles Containing Bioactive Compounds Obtained from Marine Sources to Manage Neurodegenerative Diseases - Joana Torres; Inês Costa; Andreia F. Peixoto; Renata Silva; José Manuel Sousa Lobo; Ana Catarina Silva (MDPI AG, 2023)
Marine sources contain several bioactive compounds with high therapeutic potential, such as remarkable antioxidant activity that can reduce oxidative stress related to the pathogenesis of neurodegenerative diseases. Indeed, there has been a growing interest in these natural sources, especially those resulting from the processing of marine organisms (i.e., marine bio-waste), to obtain natural antioxidants as an alternative to synthetic antioxidants in a sustainable approach to promote circularity by recovering and creating value from these bio-wastes. However, despite their expected potential to prevent, delay, or treat neurodegenerative diseases, antioxidant compounds may have difficulty reaching the brain due to the need to cross the blood-brain barrier (BBB). In this regard, alternative delivery systems administered by different routes have been proposed, including intranasal administration of lipid nanoparticles, such as solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC), which have shown promising results. Intranasal administration shows several advantages, including the fact that molecules do not need to cross the BBB to reach the central nervous system (CNS), as they can be transported directly from the nasal cavity to the brain (i.e., nose-to-brain transport). The benefits of using SLN and NLC for intranasal delivery of natural bioactive compounds for the treatment of neurodegenerative diseases have shown relevant outcomes through in vitro and in vivo studies. Noteworthy, for bioactive compounds obtained from marine bio-waste, few studies have been reported, showing the open potential of this research area. This review updates the state of the art of using SLN and NLC to transport bioactive compounds from different sources, in particular, those obtained from marine bio-waste, and their potential application in the treatment of neurodegenerative diseases.